The Impact of Sodium Alginate Hydrogel on Exogenous Glucose Oxidation Rate and Gastrointestinal Comfort in Well-Trained Runners - Sutehall, Shaun; Muniz-Pardos, Borja; Bosch, Andrew N.; Galloway, Stuart D.; Pitsiladis, Yannis (Frontiers in Nutrition, 2022)
Purpose. To quantify the effect of adding sodium alginate and pectin to a carbohydrate (CHO) beverage on exogenous glucose (ExGluc) oxidation rate compared with an isocaloric CHO beverage. Methods. Following familiarization, eight well-trained endurance athletes performed four bouts of prolonged running (105 min; 71±4% of V̇O2max) while ingesting 175 mL of one of the experimental beverages every 15 min. In randomized order, participants consumed either 70 g.hr-1 of maltodextrin and fructose (10% CHO; NORM), 70 g.hr-1 of maltodextrin, fructose, sodium alginate and pectin (10% CHO; ENCAP), 180 g.hr-1 of maltodextrin, fructose, sodium alginate and pectin (26% CHO; HiENCAP), or water (WAT). All CHO beverages had a maltodextrin/fructose ratio of 1:0.7 and contained 1.5 g.L-1 of sodium chloride. Total substrate oxidation, ExGluc oxidation rate, blood glucose, blood lactate, serum non-esterified fatty acid (NEFA) concentration and RPE were measured every 15 min. Every 30 min, participants provided information regarding their gastrointestinal discomfort (GID). Results. There was no significant difference in peak ExGluc oxidation between NORM and ENCAP (0.63±0.07 and 0.64±0.11 g.min-1, respectively; p>0.5), both of which were significantly lower than HiENCAP (1.13±0.13 g.min-1, p<0.01). Both NORM and HiENCAP demonstrated higher total CHO oxidation than WAT from 60 and 75 min respectively until the end of exercise, with no differences between CHO trials. During the first 60 min, blood glucose was significantly lower in WAT compared with NORM and HiENCAP but no differences between CHO beverages. Both ENCAP and HiENCAP demonstrated a higher blood glucose concentration from 60-105 min than WAT and ENCAP was significantly higher than HiENCAP. There were no significant differences in reported GID symptoms between the trials. Conclusions. At moderate ingestion rates (i.e., 70 g.hr-1), the addition of sodium alginate and pectin did not influence the ExGluc oxidation rate compared with an isocaloric CHO beverage. At very high ingestion rates (i.e., 180 g.hr-1), high rates of ExGluc oxidation were achieved in line with the literature.